IMPLEMENTATION OF ISLAMIC EDUCATION THROUGH BOARDING SCHOOL SYSTEM - Hanun, Farida (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2019)
AbstractThis study aimed to evaluate the implementation of Islamic education through boarding school system at SMA Islam Nurul Fikri in Lembang, Bandung. This study is conducted by using a qualitive method. The study revealed five major results namely; a) SMA Islam Nurul Fikri has been attracted citizens because of their Â integrated system in the curriculum that is combined general and religious education; b) studentsâ€™ family backgrounds are from the upper and middle classes with high intelligence; c) experiential learning processes that are integrated cognitive, affective and conative domains; d) the outputs of majority students are enrolled in the state universities and won many achievements in various provincial and national competitions; and e) the expected model in the future is to maintain an integrated school model through a boarding school system in producing students who are proficient in the general and religious fields and expanding access for middle and lower-class students.Abstrak Penelitian ini bertujuan untuk mengetahui penyelenggaraan pendidikan Islam melalui sistem Boarding school. Lokasi di SMA Islam Nurul Fikir Lembang dengan metode kualitatif. Hasil penelitian menunjukkan: a) SMA Islam Nurul Fikri banyak diminati masyarakat karena adanya sistem boarding school dan kurikulum terpadu yang memadukan pendidikan umum dan pendidikan agama; b) input peserta didik berasal dari kalangan menengah atas dengan kecerdasan tinggi; c) proses pembelajaran melalui pengalaman (experiential learning) dan memadukan secara utuh ranah kognitif, afektif dan konatif; d) output peserta didik banyak yang masuk ke Perguruan Tinggi Negeri dan banyak meraih prestasi berbagai kejuaraan lomba baik tingkat provinsi maupun nasional; e) model yang diharapkan ke depan adalah mempertahankan model sekolah terpadu melalui sistem boarding school dengan menghasilkan peserta didik yang mahir di bidang umum dan agama serta memperluas akses bagi peserta didik menengah ke bawah.